2016
DOI: 10.1080/14681366.2016.1155639
|View full text |Cite
|
Sign up to set email alerts
|

Towards a well-being focussed language pedagogy: enabling arts-based, multilingual learning spaces for young people with refugee backgrounds

Abstract: Frimberger, Katja (2016) Towards a well being focussed language pedagogy: Enabling artsbased, multilingual learning spaces for young people with refugee backgrounds, Pedagogy, Culture, Society, Volume 24, Issue 2, pp. [285][286][287][288][289][290][291][292][293][294][295][296][297][298][299] Link to publication: http://www.tandfonline.com/doi/abs/ AbstractThe following article explores the conceptual background and pedagogical realities of establishing a well-being focussed language pedagogy in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…In his study, Frimberger (2016) illustrated that the level of education obtained by the refugee students in their own language or home country, plays a crucial role in learning the target language or foreign language. Similarly, Olliff and Couch (2005) found that refugees, who did not have any formal learning in their own language or home country, face more challenges than who had formal learning in their own language in terms of learning foreign language.…”
Section: Literature Review Problems Facing Refugees In Learning a Formentioning
confidence: 99%
“…In his study, Frimberger (2016) illustrated that the level of education obtained by the refugee students in their own language or home country, plays a crucial role in learning the target language or foreign language. Similarly, Olliff and Couch (2005) found that refugees, who did not have any formal learning in their own language or home country, face more challenges than who had formal learning in their own language in terms of learning foreign language.…”
Section: Literature Review Problems Facing Refugees In Learning a Formentioning
confidence: 99%
“…In conclusion, it should be noted that education in emergencies has to consider refugee children's needs in their entirety and to address social and emotional issues involved in the learning processes. Meanwhile, language learning activities incorporating music, drama, theater or art can help young refugee children cope with trauma and fears (Delaney 2016;Frimberger 2016). In this vein, drama can be considered not only as an effective pedagogical method to facilitate communication (Ntelioglou et al 2014), but also as a teaching procedure to make refugee children regain hope for the future (Papadopoulou et al 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Such practices might be taken for granted by students who have not experienced insecurity or exclusion, but they can be poignant for refugees (Hayward 2017). Crucial for making this happen is that teachers have opportunities for professional development to understand and address the needs of refugee students, that they have the time and flexibility to depart from schedules and focus on the child, and that the whole school community is committed to this approach (Wilkinson and Kaukko 2020;Baak 2016;Frimberger 2016). When this happens, education can provide the scaffolding needed to regrow day-to-day rhythms and patterns for refugee students (Dryden-Peterson 2016; Pastoor 2017).…”
Section: Love Pedagogy and Refugee Childrenmentioning
confidence: 99%